2006
DOI: 10.1038/sj.bjc.6603325
|View full text |Cite|
|
Sign up to set email alerts
|

Somatostatin receptor expression, tumour response, and quality of life in patients with advanced hepatocellular carcinoma treated with long-acting octreotide

Abstract: Octreotide may extend survival in hepatocellular carcinoma (HCC). Forty-one per cent of HCCs have high-affinity somatostatin receptors. We aimed to determine the feasibility, safety, and activity of long-acting octreotide in advanced HCC; to identify the best method for assessing somatostatin receptor expression; to relate receptor expression to clinical outcomes; and to evaluate toxicity. Sixty-three patients with advanced HCC received intramuscular long-acting octreotide 20 mg monthly until progression or to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 22 publications
(27 reference statements)
0
28
0
Order By: Relevance
“…The rate of octreotide scan positivity has not been studied in Asian population, while in the Western population it seems to be between 35 and 56% (Nguyen-Khac et al, 2009;Cebon et al, 2006), matching with the rate of positivity in the immunohistochemistry studies.…”
Section: Somatostatin Receptors (Ssts)mentioning
confidence: 51%
“…The rate of octreotide scan positivity has not been studied in Asian population, while in the Western population it seems to be between 35 and 56% (Nguyen-Khac et al, 2009;Cebon et al, 2006), matching with the rate of positivity in the immunohistochemistry studies.…”
Section: Somatostatin Receptors (Ssts)mentioning
confidence: 51%
“…Cebon et al [34] reported that 41% of the HCC tissue samples overexpressed SSTR with high affinity for octreotide. Further studies found high detection rates of SSTR 2, 3 and 5 in HCC cells, although with high heterogenicity even in the same tumor.…”
Section: Discussionmentioning
confidence: 99%
“…For the long-acting somatostatin analogue octreotide, which revealed conXicting clinical results (Kouroumalis et al 1998;Dimitroulopoulos et al 2002Dimitroulopoulos et al , 2007Raderer et al 2000;Yuen et al 2002;Verset et al 2007;Treiber et al 2007;Becker et al 2007;Cebon et al 2006;Plentz et al 2005;Slijkhuis et al 2005;Rabe et al 2002;Pan et al 2003;Samonakis et al 2002), we and others demonstrated that clinical response was associated with a reduction in systemic vascular endothelial growth factor (VEGF)-A secretion (Treiber et al 2006;Jia et al 2003;Poon et al 2004Poon et al , 2001. Sorafenib, a combined small molecule VEGF/ RAF kinase inhibitor resulted in a moderate prolongation of survival in Child A patients (Abou-Alfa et al 2006;Llovet et al 2007).…”
Section: Introductionmentioning
confidence: 91%